Deep brain stimulation for medically refractory life-threatening status dystonicus in children - Walcott, Brian P. (2012)
Generalized dystonic syndromes may escalate into persistent episodes of generalized dystonia known as status dystonicus that can be life-threatening due to dystonia-induced rhabdomyolysis and/or respiratory compromise. Treatment of these conditions usually entails parenteral infusion of antispasmodic agents and sedatives and occasionally necessitates a medically induced coma for symptom control. The authors report a series of 3 children who presented with medically intractable, life-threatening status dystonicus and were successfully treated with bilateral pallidal deep brain stimulation. Bilateral globus pallidus internus stimulation appears to be effective in the urgent treatment of medically refractory and life-threatening movement disorders.